2010
DOI: 10.1002/j.2161-1912.2010.tb00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Counseling and Psychoanalysis: Advancing the Value of Diversity

Abstract: Arguably, the defining feature of the counseling profession is an appreciation for human diversity. Early counseling movements emphasized individual diversity, while multiculturalism and social justice highlighted cultural diversity. The author maintains that contemporary psychoanalytic thought can supply a needed intraindividual diversity perspective, which has been suppressed by dominant ideologies.Podría decirse que el rasgo definitorio de la profesión de la consejería es la apreciación por la diversidad hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Although much of the psychoanalytic literature has focused on cultural experience from a dominant psychoanalytic tradition, such as classical theory or relational psychoanalysis, the complexity of cultural identity formation requires multiple psychoanalytic perspectives and an integration of clinical and research knowledge rooted in other traditions (e.g., feminist psychology, feminist psychology, multicultural psychology, social psychology, critical psychology). Hansen (2010) pointed out that the term identity assumes a value of unity rather than diversity, and highlights the role of unconscious conflict in “intraindividual diversity” (p. 16). He suggested that the centrality of internal conflict is shared across different psychoanalytic theories, and that postmodern and relational approaches in particular emphasize the importance of multiplicity of subjective experience.…”
Section: Recognize the Complex Ways That Intersecting Cultural Identi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although much of the psychoanalytic literature has focused on cultural experience from a dominant psychoanalytic tradition, such as classical theory or relational psychoanalysis, the complexity of cultural identity formation requires multiple psychoanalytic perspectives and an integration of clinical and research knowledge rooted in other traditions (e.g., feminist psychology, feminist psychology, multicultural psychology, social psychology, critical psychology). Hansen (2010) pointed out that the term identity assumes a value of unity rather than diversity, and highlights the role of unconscious conflict in “intraindividual diversity” (p. 16). He suggested that the centrality of internal conflict is shared across different psychoanalytic theories, and that postmodern and relational approaches in particular emphasize the importance of multiplicity of subjective experience.…”
Section: Recognize the Complex Ways That Intersecting Cultural Identi...mentioning
confidence: 99%
“…research knowledge rooted in other traditions (e.g., feminist psychology, feminist psychology, multicultural psychology, social psychology, critical psychology). Hansen (2010) pointed out that the term identity assumes a value of unity rather than diversity, and highlights the role of unconscious conflict in "intraindividual diversity" (p. 16). He suggested that the centrality of internal conflict is shared across different psychoanalytic theories, and that postmodern and relational approaches in particular emphasize the importance of multiplicity of subjective experience.…”
Section: Recognize the Complex Ways That Intersecting Cultural Identi...mentioning
confidence: 99%
“…If the counseling profession were to embrace this postmodernist vision of professional identity, identity diversity within the same individual would be tolerated and appreciated, just as diversity between people is championed by the multicultural movement. Indeed, it is ironic that the counseling profession has embraced diversity between people in the form of multicultural-ism but has generally rejected diversity within individuals as it relates to professional identity (Hansen, 2010). This irony is richly illustrated by the most recent Council for Accreditation of Counseling and Related Educational Programs (CACREP) standards for counseling programs (CACREP, 2009).…”
Section: Congruent Versus Dialogicmentioning
confidence: 99%